2021
DOI: 10.1101/2021.07.08.451607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrastructural analysis of nasopharyngeal epithelial cells from patients with SARS-CoV-2 infection

Abstract: The nasal epithelium is an initial site for SARS-CoV-2 infection, responsible for the ongoing COVID-19 pandemic. However, the pathogenicity and morphological impact of SARS-CoV-2 on the nasopharynx cells from symptomatic patients with different viral loads remain poorly understood. Here, we investigated the ultrastructure of nasal cells obtained from individuals at distinct disease days and with high and low SARS-CoV-2 loads. Squamous and ciliated cells were the main cells observed in SARS-CoV-2 negative sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A SARS-coronavirus specific antibody is applied to a thin section, followed by a secondary antibody conjugated to colloidal gold particles. The gold particles appear as electron dense black dots in areas where coronavirus is present or where the protein that the primary antibody targets is present, such as nucleocapsid inclusions (Figure 4a Respiratory system changes due to SARS-CoV-2 infection have been most thoroughly described (Ackermann et al, 2020;Martines et al, 2020;Santana et al, 2021;Saraiva et al, 2021). Type I pneumocyte degeneration, type II pneumocyte hyperplasia, and hyaline membrane formation were common ultrastructural features of SARS-CoV-2 infection (Martines et al, 2020;Santana et al, 2021).…”
Section: Complementary Methods For Virus Detectionmentioning
confidence: 99%
See 4 more Smart Citations
“…A SARS-coronavirus specific antibody is applied to a thin section, followed by a secondary antibody conjugated to colloidal gold particles. The gold particles appear as electron dense black dots in areas where coronavirus is present or where the protein that the primary antibody targets is present, such as nucleocapsid inclusions (Figure 4a Respiratory system changes due to SARS-CoV-2 infection have been most thoroughly described (Ackermann et al, 2020;Martines et al, 2020;Santana et al, 2021;Saraiva et al, 2021). Type I pneumocyte degeneration, type II pneumocyte hyperplasia, and hyaline membrane formation were common ultrastructural features of SARS-CoV-2 infection (Martines et al, 2020;Santana et al, 2021).…”
Section: Complementary Methods For Virus Detectionmentioning
confidence: 99%
“…Type I pneumocyte degeneration, type II pneumocyte hyperplasia, and hyaline membrane formation were common ultrastructural features of SARS‐CoV‐2 infection (Martines et al, 2020 ; Santana et al, 2021 ). A recent study of nasopharyngeal epithelial cells from SARS‐CoV‐2 infected individuals showed loss of microvilli and the primary cilium in squamous cells as well as an increase in the number of multivesicular bodies and autophagosomes when compared with specimens from SARS‐CoV‐2 negative individuals (Saraiva et al, 2021 ). Santana et al further noted disruption of the epithelial‐endothelial barrier, in addition to cellular debris and fibrin in the alveolar space and detachment of type II pneumocytes from the basement membrane (Santana et al, 2021 ).…”
Section: Ultrastructural Changes Caused By Sars‐cov ...mentioning
confidence: 99%
See 3 more Smart Citations